2008
DOI: 10.2131/jts.33.71
|View full text |Cite
|
Sign up to set email alerts
|

Role of TNF-α and extracellular ATP in THP-1 cell activation following allergen exposure

Abstract: -Dendritic cells (DCs), including Langerhans cells (LCs), play a critical role in the induction phase of allergic contact hypersensitivity. Following exposure to chemical allergens in the skin, LCs undergo a maturation process leading to the up-regulation of expression of co-stimulatory molecules, such as CD86, CD54 and CD40. Our previous study revealed that chemical allergens induce phenotype alterations (e.g., CD86, CD54 and CD40) and cytokine production (TNF-α and IL-8) in THP-1 cells that possibly reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…RANTES has been previously identified in vivo as being a key cytokine in the murine ear test to DNCB (Baumer et al, 2004) thus supporting its relevance as an in vitro biomarker. In order to compare the sensitizer predictability of RANTES with a currently used cytokine (Mitjans et al, 2008, Toebak et al, 2006, Miyazawa et al, 2008 we investigated the generation of IL-8 on MUTZ-3 cells. Our unpublished data showed that IL-8 was increased comparably to the sensitizers seen for RANTES, thus, RANTES can be considered as extending the in vitro biomarkers available for sensitizer testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RANTES has been previously identified in vivo as being a key cytokine in the murine ear test to DNCB (Baumer et al, 2004) thus supporting its relevance as an in vitro biomarker. In order to compare the sensitizer predictability of RANTES with a currently used cytokine (Mitjans et al, 2008, Toebak et al, 2006, Miyazawa et al, 2008 we investigated the generation of IL-8 on MUTZ-3 cells. Our unpublished data showed that IL-8 was increased comparably to the sensitizers seen for RANTES, thus, RANTES can be considered as extending the in vitro biomarkers available for sensitizer testing.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have identified a number of cytokines of importance in the sensitization process which may constitute an important aspect of in vitro test development. Recent studies suggested that IL-8 detection following sensitizer or nonsensitizer application to THP-1 cells could function as a promising in vitro model to assist with sensitization screening (Mitjans et al, 2008, Miyazawa et al, 2008, Toebak et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that augmentation of protein expression due to contact allergen exposure does not depend on humoral factors from dead caused by allergen exposure. Miyazawa et al (2008b) reported that the TNF-α from THP-1 cells activated by contact allergens was related to CD86 and CD54 expression. But in contrast, there is no induction of CD86 and CD54 expression after incubation with humoral factors from dead cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that expression of CD86 and the production of IL-1β and IL-8 are induced in U937 cells when exposed to sensitizers, such as 2,4,6-Trinitrobenzene sulfonic acid (TNBS), DNCB, Eugenol (EU), Citral and so on (Python et al, 2007). In addition, cell signaling events inducing such phenotypic alterations were investigated using THP-1 cell line (Miyazawa et al, 2008a(Miyazawa et al, , 2008b. These phenotypic alterations are expected to be the indicators for the identification of contact sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK, ERK, PGK, and NFκB) (Trompezinski et al, 2008;dos Santos et al, 2009). co-workers (2008a and2008b) examined P38 MAPK, a mitogen-activated protein kinase, and ERK, an extracellular signal-regulated kinase in THP-1 cells. It is important to note that moderate and weak sensitizers needed 10x and 100x higher exposure concentrations, respectively, than strong sensitizers to activate kinase pathways.…”
Section: Step 6; Key Event 2) Events In Keratinocytementioning
confidence: 99%